Effect of on-pump vs. off-pump coronary artery bypass grafting in patients with non-dialysis-dependent severe renal impairment: propensity-matched analysis from the UK registry dataset - Fudulu, Daniel P.; Argyriou, Amerikos; Kota, Rahul; Chan, Jeremy; Vohra, Hunaid; Caputo, Massimo; Zakkar, Mustafa; Angelini, Gianni D. (Frontiers in Cardiovascular Medicine, 2024)
Introduction On-pump coronary artery bypass (ONCABG) grafting in patients with a pre-existing poor renal reserve is known to carry significant morbidity and mortality. There is limited controversial evidence on the benefit of off-pump coronary artery bypass (OPCABG) grafting in these high-risk groups of patients. We compared early clinical outcomes in propensity-matched cohorts of patients with non-dialysis-dependent pre-operative severe renal impairment undergoing OPCABG vs. ONCABG, captured in a large national registry dataset. Methods All data for patients with a pre-operative creatinine clearance of less than 50 mL/min who underwent elective or urgent isolated OPCABG or ONCABG from 1996 to 2019 were extracted from the UK National Adult Cardiac Surgery Audit (NACSA) database. Propensity score matching was performed using 1:1 nearest neighbor matching without replacement using several baseline characteristics. We investigated the effect of ONCABG vs. OPCABG in the matched cohort using cluster-robust standard error regression. Results We identified 8,628 patients with severe renal impairment undergoing isolated CABG, of whom 1,142 (13.23%) underwent OPCABG during the study period. We compared 1,141 propensity-matched pairs of patients undergoing OPCABG vs. ONCABG. The median age of the matched population was 78 years in both groups, with no significant imbalance post-matching in the rest of the variables. There was no difference between OPCABG and ONCABG in in-hospital mortality rates, post-operative dialysis, and stroke rates. However, the return to theatre for bleeding or tamponade was higher in ONCABG vs. OPCABG (P > 0.02); however, OPCABG reduced the total length of stay in the hospital by 1 day (P = 0.008). After double adjustment in the matched population using cluster-robust standard regression, ONCABG did not increase mortality compared to OPCABG (OR, 1.05, P = 0.78), postoperative stroke (OR, 1.7, P = 0.12), and dialysis (OR, 0.7, P = 0.09); however, ONCABG was associated with an increased risk of bleeding (OR, 1.53, P = 0.03). Discussion In this propensity analysis of a large national registry dataset, we found no difference in early mortality and stroke in patients with pre-operative severe renal impairment undergoing OPCABG or ONCABG surgery; however, ONCABG was associated with an increased risk of return to theatre for bleeding and an increased length of hospital stay.